A new version of a low concentration evacuated tube solar collector: Optical and thermal investigation. (1st March 2019) - Teles, Mavd de Paula Ribeiro; Ismail, Kamal A.R.; Arabkoohsar, Ahmad
Highlights: The absorber is eccentrically surrounded by a transparent glass cover. A reflective film insert keeps uniform temperature on absorber surface. Four possible tracking systems are evaluated. The annual efficiency of the solar collector is about 61.5%. The maximum and minimum daily efficiencies are about 73% and 42%. Abstract: This work is focused on investigating the performance of a new version of evacuated tube solar collector with and without solar tracking system. The evacuated tube solar collector is composed of an absorbing copper tube positioned eccentrically inside a transparent glass cover tube which has a reflective film insert on its inner surface and vacuum in eccentric annular space. Modeling of the proposed evacuated tube collector is based on the conservation equations of mass, momentum and energy and discretized by using the finite volumes method. A home-built numerical code is developed, tested and its grid size optimized. This code is validated against available experimental and numerical results. Effects of the tilt angle and tracking systems are also evaluated. The results showed maximum and minimum daily efficiencies of the collector of about 73% and 42%, respectively. The annual efficiency of this collector was evaluated as 61.5% for the city of São Luís, Brazil. The new contributions from the present work include the reflective film, the eccentricity of the absorber and the presence of vacuum in the annular space. The reflective film helps to keep the absorber at uniform temperature and reduce thermal induced stress. The eccentricity is introduced to create concentration effect which helps to increase the outlet temperature of the working fluid and reduce the mass of the collector system. The presence of vacuum in the eccentric annular space reduces effectively the thermal losses, improves the efficiency.